Republic of Congo : Enhanced Heavily Indebted Poor Countries Initiative; Completion Point Document and Multilateral Debt Relief Initiative. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper discusses Congo's progress under the Enhanced Initiative for Heavily Indebted Poor Countries (HIPC). In the view of the staff of IDA and the IMF, Congo has met in full all of the triggers for reaching the completion point. All key decisions, actions, and measures required to observe the triggers have been taken, including a satisfactory track record of implementation for public investment management, procurement, governance and anticorruption, improvement in the internal controls and accounting of the state-owned oil company, and oil commercialization.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet